KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PENGHINAAN YANG DILAKUKAN MELALUI MEDIA SOSIAL - Bayu Anggara (Cattleya Darmaya Fortuna, 2025)
The main purpose of law is to create an orderly, safe, and structured life. However, the development of community needs in Indonesia has triggered challenges in the form of a moral crisis that affects social behavior, including acts of insult or defamation. This insult involves attacks on a person's honor and reputation through various means, both verbally and through social media. Law enforcement against this criminal act of insult is regulated in Article 310 paragraph (1) of the Criminal Code, which is universal without distinguishing between certain legal subjects. In addition, Article 27A of Law Number 1 of 2024, as the second revision of Law Number 11 of 2008 concerning Information and Electronic Transactions, specifically regulates insults through electronic media. This rule provides a basis for legal certainty for positive law enforcement in dealing with violations involving communication and information technology. This study examines the importance of a positive legal approach in encouraging the effectiveness of handling insults that occur in the realm of social media.